2020
DOI: 10.1016/j.bjid.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 leading to acute pancreatitis: an unusual presentation

Abstract: During SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2) pandemic, the etiologic agent of COVID-19, several studies described the involvement of other tissues besides the respiratory tract, such as the gastrointestinal tract. Angiotensin-converting enzyme-2, the functional virus host cell receptor expressed by organs and tissues, seems to have an important role in the pathophysiology and presentation of this disease. In pancreas, this receptor is expressed in both exocrine glands and islets, being a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 19 publications
0
41
0
4
Order By: Relevance
“…[42][43][44][45] Since the beginning of the pandemic, associations have been drawn between COVID-19 infection and pancreatic injury and pancreatitis. Case reports have detailed the development of clinical pancreatitis following COVID-19 infection, [46][47][48][49][50] and several studies have suggested that elevations in amylase and lipase may be a fairly common feature of infection. 51,52 As noted above in studies focused on the islet, data on whether ACE2 is enhanced or decreased in pancreatic exocrine cells are conflicting, with some datasets suggesting an increase in ACE2 expression in the exocrine pancreas 40,53,54 and others suggesting relative depletion among the exocrine cells.…”
Section: Effects On β Cells Due To Infection Of Surrounding Cellsmentioning
confidence: 99%
“…[42][43][44][45] Since the beginning of the pandemic, associations have been drawn between COVID-19 infection and pancreatic injury and pancreatitis. Case reports have detailed the development of clinical pancreatitis following COVID-19 infection, [46][47][48][49][50] and several studies have suggested that elevations in amylase and lipase may be a fairly common feature of infection. 51,52 As noted above in studies focused on the islet, data on whether ACE2 is enhanced or decreased in pancreatic exocrine cells are conflicting, with some datasets suggesting an increase in ACE2 expression in the exocrine pancreas 40,53,54 and others suggesting relative depletion among the exocrine cells.…”
Section: Effects On β Cells Due To Infection Of Surrounding Cellsmentioning
confidence: 99%
“…There are few reported cases where inflammation of the ectopic tissue was identified either in isolation 9 or simultaneously 10 with inflammation of the anatomical pancreas. During the COVID-19 pandemic, we have also seen cases of SARS-CoV-2 infection associated with acute pancreatitis, 11 12 with growing evidence to suggest that the novel coronavirus could be a cause of acute pancreatitis. We believe that the abundant ACE2 expression in pancreatic cells and SARS-CoV-2 using ACE2 to enter human cells is a plausible mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cells present high expression of ACE2 receptors and this creates potential for pancreatic injury in the course of COVID-19 (3). However up to date only few COVID-19 related pancreatitis were reported and none in HIV-positive person (4,5). As of today the incidence of pancreatitis and its future clinical implications in this speci c subgroup of patients remain unknown.…”
Section: Discussionmentioning
confidence: 99%